Assessment of Allergen-Responsive Regulatory T Cells in Experimental Asthma Induced in Different Mouse Strains - C. T. Azevedo; A. C. Cotias; A. C. S. Arantes; T. P. T. Ferreira; M. A. Martins; P. C. Olsen (Mediators of Inflammation)
Background. Regulatory T cells (Tregs) are important in regulating responses to innocuous antigens, such as allergens, by controlling the Th2 response, a mechanism that appears to be compromised in atopic asthmatic individuals. Different isogenic mouse strains also have distinct immunological responses and susceptibility to the experimental protocols used to develop lung allergic inflammation. In this work, we investigated the differences in the frequency of Treg cell subtypes among A/J, BALB/c, and C57BL/6, under normal conditions and following induction of allergic asthma with ovalbumin (OVA). Methods. Subcutaneous sensitization followed by 4 consecutive intranasal OVA challenges induced asthma characteristic changes such as airway hyperreactivity, inflammation, and production of Th2 cytokines (IL-4, IL-13, IL-5, and IL-33) in the lungs of only A/J and BALB/c but not C57BL/6 strain and evaluated by invasive whole-body plethysmography, flow cytometry, and ELISA, respectively. Results. A/J strain naturally showed a higher frequency of CD4+IL-10+ T cells in the lungs of naïve mice compared to the other strains, accompanied by higher frequencies of CD4+IL-4+ T cells. C57BL/6 mice did not develop lung inflammation and presented higher frequency of CD4+CD25+Foxp3+ Treg cells in the bronchoalveolar lavage fluid (BALF) after the allergen challenge. In in vitro settings, allergen-specific stimulation of mediastinal LN (mLN) cells from OVA-challenged animals induced higher frequency of CD4+IL-10+ Treg cells from A/J strain and CD4+CD25+Foxp3+ from C57BL/6. Conclusions. The observed differences in the frequencies of Treg cell subtypes associated with the susceptibility of the animals to experimental asthma suggest that CD4+CD25+Foxp3+ and IL-10-producing CD4+ Treg cells may play different roles in asthma control. Similar to asthmatic individuals, the lack of an efficient regulatory response and susceptibility to the development of experimental asthma in A/J mice further suggests that this strain could be preferably chosen in experimental models of allergic asthma.